E-Recruitment in Practice: A Study on Jobseekers’ Perception in Bangladesh - Karim, Mohammad Rezaul; Miah, Md. Shelim; Khatun, Asma (Global Disclosure of Economics and Business, 2015)
The rapid growth and use of the Internet over the last several years has changed the way companies’ conduct of business activities, including the activities of human resource management. To attract and recruit best employees is one of the great challenges for Human Resource Department. Today online recruiting has become a significant tool for Human Resource Department. Bangladeshi companies also can recruit with their websites, job boards or resume banks, newspaper classified ads, and job boards. Online recruiting processes increase firms' competitive advantage through increased efficiency and lower costs and offers benefits and opportunities to jobseekers. This paper investigates the perceptions and behaviors of job-seekers concerning the use of the Internet as a recruiting source. 204 survey questionnaires were distributed to job seekers who are almost regularly using Internet for various purposes. The results showed that perceived usefulness and perceived enjoyment are positively and significantly related to the behavioral intention to use Internet as a job search tool. The study implies that the developers of online job sites need to provide additional useful functionalities or tools in the sites to help users for job search. The paper provides an insight for jobseekers to find employment by using Internet as a job search tool.